2012
DOI: 10.1016/j.tate.2012.02.007
|View full text |Cite
|
Sign up to set email alerts
|

How emotionally intelligent are pre-service teachers?

Abstract: Although there is evidence that teacher emotional intelligence is important for pupil adjustment and learning and for teachers in managing the emotional demands of their work, little is known about the levels of emotional skill of teachers and beginning teachers. Using Mayer and Salovey's emotional intelligence (EI) model and the MSCEIT test of EI, this study investigates how emotionally skilled student teachers are (N = 352). Results show lower than average levels of EI among student teachers, but with import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(40 citation statements)
references
References 87 publications
0
38
0
2
Order By: Relevance
“…Rather, these emotionally adaptive mentors combine their focus on emotional aspects of novice teacher learning with attention for encouraging novice teacher reflective thought, and for progressively developing novice teacher competence. We suggest that in light of recent concerns about the level of emotional intelligence of novice teachers (Corcoran & Tormey, 2012) future research should pay special attention to how such emotionally adaptive mentors might help novice teachers with the development of emotional skills in teaching and learning to teach. We also suggest that such future research should attend to mentor gender, as we found that the emotionally adaptive mentors were all female, whereas the cognitively adaptive mentors were all male.…”
Section: Discussionmentioning
confidence: 96%
“…Rather, these emotionally adaptive mentors combine their focus on emotional aspects of novice teacher learning with attention for encouraging novice teacher reflective thought, and for progressively developing novice teacher competence. We suggest that in light of recent concerns about the level of emotional intelligence of novice teachers (Corcoran & Tormey, 2012) future research should pay special attention to how such emotionally adaptive mentors might help novice teachers with the development of emotional skills in teaching and learning to teach. We also suggest that such future research should attend to mentor gender, as we found that the emotionally adaptive mentors were all female, whereas the cognitively adaptive mentors were all male.…”
Section: Discussionmentioning
confidence: 96%
“…emotional exhaustion) (Chan, 2006), and the impact of teachers' emotional intelligence on teaching satisfaction and teachers' use of emotional labour strategies, particularly the expression of naturally felt emotions (Yin, Lee, Zhang, & Jin, 2013). Corcoran and Tormey (2012;2013) study the emotional intelligence and emotional skills of pre-service teachers. In addition, there is research into the emotional environment within the classroom: the importance of various aspects of teachers' emotional skills and competence for educational practice are evaluated (Harvey, Bimler, Evans, Kirkland, & Pechtel, 2012).…”
Section: Teachers' Emotional Intelligence Skills and Knowledgementioning
confidence: 99%
“…(Eren, 2014a , p. 73) The psychological research agenda on identifying emotions as well as their relation with behavior is maybe most clearly exemplifi ed in the recent work on student teachers' emotional intelligence. Corcoran and Tormey ( 2012 ) measured the emotional intelligence of 352 Irish student teachers, concluding that their scores were lower than average, but with important inter-individual differences. Similar fi ndings were obtained in a study of 210 Romanian student teachers, measuring both emotional intelligence and maturity: somewhat higher (average or slightly above), but also with large inter-individual differences (Dumitriu, Timofti, & Dumitriu, 2014 ).…”
Section: Identifying Emotions and Their Link With Behaviormentioning
confidence: 99%